The Resolution Approach to Cystic Fibrosis Inflammation - Recchiuti, Antonio; Patruno, Sara; Plebani, Roberto; Romano, Mario (Frontiers in Pharmacology, 2020)
Despite the high expectations associated with the recent introduction of CFTR modulators, airway inflammation still remains a relevant clinical issue in cystic fibrosis (CF). The classical anti-inflammatory drugs have shown very limited efficacy, when not being harmful, raising the question of whether alternative approaches should be undertaken. Thus, a better knowledge of the mechanisms underlying the aberrant inflammation observed in CF is pivotal to develop more efficacious pharmacology. In this respect, the observation that endogenous pro-resolving pathways are defective in CF and that pro-resolving mediators, physiologically generated during an acute inflammatory reaction, do not completely suppress inflammation, but promote resolution, tissue healing and microbial clearance, without compromising immune host defense mechanisms, opens interesting therapeutic scenarios for CF. In this mini-review, we present the current knowledge and perspectives of pro-resolving pharmacology in CF, focusing on the specialized pro-resolving lipid mediators and selected peptides.